Contact and Community: The Role of Social Interactions for a Political Identity. Issue 3 (26th August 2015) - Stoeckel, Florian
Abstract : Can social interaction contribute to a sense of community that transcends national borders? This question was initially raised by Deutsch (1953) and revived by Fligstein (2008). My analysis makes two contributions to this literature. First, insights from social psychology are applied to specify the microfoundations for why contact across group boundaries can be related to a collective identity. Second, a new three‐wave panel data set is used to examine the relationship empirically. The sample includes almost 1, 500 students at 38 German universities. The results show that social interaction contributes to a European identity, but that it is in particular contact with other international students rather than contact with hosts that fosters it most effectively. The data also reveal that contact has a more profound impact on individuals with a weak European identity to begin with. Finally, the change I find is stable after students return to their home institutions.